El debate y la deliberación entre estudiantes en los procesos de enseñanza y aprendizaje en la educación básica primaria: Análisis bibliográfico (2021)
This work is a compilation monograph in which an analysis of bibliographic references is presented in order to investigate how debate and deliberation are used among students of basic primary education in the teaching-learning processes. For this purpose, categories of analysis are proposed to cover different perspectives of debate and deliberation. A matrix is also created as a systematization tool in which the consulted texts are presented with their respective category. Finally, an analysis of the documentary readings is presented for each of the proposed categories.